Immune response features in children with chronic constipation - O. V. Moskalets; V. I. Scherbina (Кубанский научный медицинский вестник, 2016)
In the article the results of examination of some immune characteristics, including some autoantibodies in 28 children with chronic constipation are represented. Increased levels of circulating immune complexes and increased spontaneous NST test were the most common immune laboratory findings. ANCA were found in 18 patients. There were no correlation between the type of constipation (dolichosigmoid, anal athresia, functional constipation), severety and character of disbiosis and ANCA rates. Thus, in most cases revealed immune disorders may indicate chronic inflammation in the bowl associated with chronic constipation. Children with increased ANCA rates seems have the higher risk of autoimmune disorders in future